Clinical profile of adults and children with reactive arthritis in India – A cohort study - Koshy Nithin Thomas; Anamika Kumari Anuja; Latika Gupta (Indian Journal of Rheumatology)
Background: An evolving clinicodemographic spectrum is reported in reactive arthritis (reA) with the changing microbial profile in recent times. Moreover, understanding of chronic disease patterns is limited due to widespread beliefs of a self-limiting nature. We thus assessed the clinical profile of a cohort of acute reA and compare them with chronic reA. Methods: A hospital-based study of prevalent triggers and demographic features, articular and extra-articular manifestations, and radiological findings was undertaken in children and adults with reA at a tertiary care center in northern India. Results: Sixty-eight cases (8 juvenile, 41 acute, and 27 chronic) of age 26 years (18–34, M:F 5.8:1) and disease duration 36 (19–60) days were enrolled. Enteritis was the most common preceding trigger (37, 54%), followed by genitourinary infection (25, 36%), irrespective of gender. The clinical spectrum mirrored previous descriptions, with arthritis in most (95%), enthesitis in 33%, and conjunctivitis and circinate balanitis being the most common extra-articular features (8% each). Numerous cases (n = 7) did not fulfill the Braun's criteria at the current visit though a high representation of sacroiliitis was noted (20%, 12%) in acute as well as chronic reA. Enthesitis was more common in the acute reA (P = 0.018) and mucocutaneous features occurred only at inception. Otherwise, the clinical profile was similar in cases triggered by urethritis and enteritis, and in children as compared with adults. Conclusion: These observations of varied spectrum of reA assume larger importance in light of the emerging concept of a unified clinic-pathologic spectrum of spondyloarthritis.